The Application of Informatics Logic in The Importation of Goods From Outside to Indonesia - Dian Damayanti; Muhammad Ridho; Zaki Zain; Jailani Arsad; Fanny Ramadhani (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2021)
Logic is a method or technique that was created to examine the accuracy of reasoning and study the principles of correct reasoning and conclusion. Logic is also called